The Relationship between Sea Surface Temperature (SST) in Pacific Ocean and Total Ozone Variations in Iran - abasali Arvin (نشریه جغرافیا و برنامه‌ریزی, 2015)
Variations of ozone layer that measure by name of total ozone (TO) oscillation are one of the modern humane concerns as one of causes or manifestations of climate change. In this research total ozone oscillation in relationship with Sea Surface Temperature (SST) in Pacific Ocean has been studied. For this aim monthly mean data from the satellites in point by 1*1.25 degree of geographical distance and monthly mean of NINO1+2, NINO3, NINO4 and NINO3.4 indices have been used. The results show that total ozone in positive\negative occurrence of SST has been increased\decreased in all Iranian areas. The asynchronous relation of effects SST indices have been tested on (TO). The strongest relations in lag time of months 5, 1, 5 and 2 respectively are for NINO1+2, NINO3, NINO4 and NINO3 indices. The correlation of NINIO1+2 with TO are better than other indices and the strongest correlation was in west and northwest of Iran. The average of synchronous and asynchronous (5 months lag time) correlation coefficient between NINIO1+2 with TO on all areas of Iran was respectively r=+0.55 and r=-0.621. The in synchronous correlation was direct and significant at 0.05 level in 86 precent of areas of Iran but asynchronous correlation was indirect and significant at 0.05 level The relation of NINO4 with (TO) was the weakest correlation in other indices.